The German Legal Services Act and the Smartlaw Case: A Precedent for Legal Tech Services in Germany - Meyer, Olaf; Luz Barreiros, Priscila (Studia Prawa Publicznego, 2025)
The legal services market in Germany is tightly regulated with the Legal Services Act (RDG) serving as the central framework for out-of-court legal services. The RDG outlines which activities are classified as legal servicesand designates the professional groups authorized to provide them. However, as digitalization and automation evolve in a significant way, the applicability of traditional laws to innovative legal services is increasingly questioned. Emerging legal tech platforms, software, and web-based applications introduce new dimensions of legal assistance, offering user-friendly, cost-effective, and accessible options, particularly for non-experts. As the RDG is not designed to encompass all conceivable aspects of legal services, but rather its primary purpose is to address and regulate existing gaps within the legal service landscape, its requirements become crucial for regulating all types of legal activities beyond the established professions such as lawyers, tax consultants, or auditors. This paper examines the challenges posed by digital legal services in the context of the RDG, focusing on key decisions by the German Federal Court of Justice (BGH) that have addressed the legality of offering a contract generator under the RDG. This article aims to analyse the Smartlaw case, emphasising the distinctive aspects of each instance’s ruling and clarifying the criteria for the RDG’s application. It also explores the boundaries of permissible legal services in Germany in the face of rapid technological advancement.